The Private Equity Market in Poland and in Central and Eastern Europe: Selected Aspects - Joanna Małecka; Teresa Łuczka (Problemy Zarządzania, 2017)
The political transformation that took place in Poland only 25 years ago allowed a re-launch and development of the most important capital market institution – the stock exchange. Today, the Warsaw Stock Exchange is the largest in Central and Eastern Europe, being among top European trading floors in terms of the number of new listings. Investors choose Poland to invest their capital both because it is the biggest economy in this region and precisely because of its developed capital market and stable and modern banking sector as well as visible activities of institutions supporting entrepreneurship. Marked growth rates of macroeconomic indicators and economic stability so far have directly influenced Poland’s attractiveness, encouraging investors to operate in the private equity market as well. Poland and countries of Central and Eastern Europe are emerging markets that are still catching up with Western Europe. The results presented in the article are based on source data from annual reports and publications that have been produced and made available by capital market institutions and from the authors’ own research on Polish entrepreneurship. The scope and volume of private equity financing in Central and Eastern Europe and in Poland are characterised by means of analyses, charts and comparisons, highlighting the importance and leading role of Poland as a country that is the first choice for private equity investors in this region.